A Sharia Economic Law Review of Online Gold Transaction Services: Integration of The Tokopedia Emas Feature Within the Pluang Ecosystem - Ilham Kurniawan Saputra; Kumedi Ja’far; Nurasari Nurasari (Hikmah, 2025)
The development of digital technology has encouraged an increase in online gold transactions as a practical and easily accessible investment alternative. However, this innovation raises new issues regarding its compatibility with the principles of Islamic economic law. This study aims to examine the application of Islamic economic law to online gold transactions through the Tokopedia Emas feature in the Pluang application. The research uses a descriptive qualitative approach with a field research design, through direct observation and in-depth interviews with five active users of Tokopedia Emas. The results show that although this platform offers convenience and flexibility in gold investment, the absence of physical delivery of gold at the time of transaction has the potential to contain elements of riba nasi'ah and gharar. In addition, rapid fluctuations in gold prices open up opportunities for speculative practices (maysir) if not accompanied by clear control mechanisms. These findings indicate that digital efficiency does not fully guarantee compliance with sharia principles. Therefore, this study recommends adjustments to the transaction mechanism, particularly regarding the clarity of contracts, ownership, and delivery of gold. The implications of this study are expected to serve as a reference for platform developers and regulators in strengthening the governance of digital gold transactions in line with the principles of Sharia economic law.